Teachers' feedback and learning in virtual workshops of thesis writing - Guadalupe Álvarez; Hilda Difabio de Anglat (Universidad de Guadalajara, 2018)
In this article, by means of a mixed methodology, we analyze teacher's feedback in the production of a chapter that the students carry out as the final activity of a virtual workshop oriented to the postgraduate thesis writing, as well as the changes they make in their texts based on this feedback. In addition, we assess whether our approximation to the student's profile, derivative of diagnosis, is associated with the feedforward or willingness to act on the received information and to use it to modify the text. The data analysis has shown that the most frequent focus of the teacher's comments is the textual model, particularly the text writing. It has also shown that this function falls into two categories: suggest corrections or offer reformulation. The most frequent change that students made is writing reformulations. Finally, it seems to be an association between student profile and feedforward. In the conclusions, important issues are highlighted: the positive impact of teacher feedback in the production of a graduate thesis chapter in a virtual workshop and the association between improvement occurrence and student profile.